Schaum's Outlines / Programming with C++ - Hubbard,Ph.D. John R. (New York : McGraw-Hill, 2000)
Like all Schaum's Outline Series books, this volume is intended to be used primarily for self study, preferably in conjunction with a regular course in C++ programming language or computer science.
includes index
Includes bibliographical references p. 405-408
aau 17/08/2022
loan
Keywords: --Programming